2021
DOI: 10.1126/sciadv.abe9459
|View full text |Cite
|
Sign up to set email alerts
|

A towering genome: Experimentally validated adaptations to high blood pressure and extreme stature in the giraffe

Abstract: The suite of adaptations associated with the extreme stature of the giraffe has long interested biologists and physiologists. By generating a high-quality chromosome-level giraffe genome and a comprehensive comparison with other ruminant genomes, we identified a robust catalog of giraffe-specific mutations. These are primarily related to cardiovascular, bone growth, vision, hearing, and circadian functions. Among them, the giraffe FGFRL1 gene is an outlier with seven unique amino acid substitutions not found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 78 publications
1
36
0
Order By: Relevance
“…Consistent with our observations, reduced fibrosis in giraffe myocardia may be linked to differences in the amino acid sequence of the ACE protein [ 32 , 44 ], as well as recently identified mutations in fibroblast growth factor receptor-like 1 (FGFRL1) [ 32 , 45 ]. Notably, the FGFRL1 protein sequence in giraffe appears to be highly divergent in comparison to a diverse array of other mammals, with seven amino acid substitutions in a region that is crucial for FGF binding.…”
Section: Introductionsupporting
confidence: 89%
“…Consistent with our observations, reduced fibrosis in giraffe myocardia may be linked to differences in the amino acid sequence of the ACE protein [ 32 , 44 ], as well as recently identified mutations in fibroblast growth factor receptor-like 1 (FGFRL1) [ 32 , 45 ]. Notably, the FGFRL1 protein sequence in giraffe appears to be highly divergent in comparison to a diverse array of other mammals, with seven amino acid substitutions in a region that is crucial for FGF binding.…”
Section: Introductionsupporting
confidence: 89%
“…It should be emphasised that most of the biomimetic examples provided in this review are correlative, which leave causation to be determined. To determine causation and ensure development of safe treatment strategies the utility of molecular genetics, as illustrated by a recent study of giraffes [184], should be part of biomimetic research. As discussed above, it will be resourceful to study the particularities and comparative patterns among organisms featured with longevity, short lifespans and unique metabolic profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Despite signs of arterial smooth muscle hypertrophy, cardiac, brain and renal damage is fully spared in giraffes [183]. A recent study identified the giraffe FGFRL1 gene as an outlier compared with other ruminants and when this mutation was inserted into the FGFRL1 gene in mice significantly less fibrosis in heart and kidneys were observed during hypertension [184]. Thus, an understanding of the protective physiology behind this may yield valuable preventive and therapeutic opportunities for treating complications related to hypertension.…”
Section: Other Lessons From the Animal Kingdom To Target The Diseasome Of Ageingmentioning
confidence: 99%
“…One major difference in human hypertensiveinduced left ventricular hypertrophy (LVH) and developmentally induced thick left ventricular wall in the giraffe is reduced cardiac fibrosis in the giraffe myocardia [71]. A recent study, which generated a high-quality giraffe genome, identified the giraffe FGFRL1 gene as an outlier compared to other ruminants [72]. When the giraffe mutation was inserted into the FGFRL1 gene in mice, significantly less renal and heart fibrosis was observed during hypertension [72].…”
Section: Cancer Protective Solutions In Naturementioning
confidence: 99%
“…A recent study, which generated a high-quality giraffe genome, identified the giraffe FGFRL1 gene as an outlier compared to other ruminants [72]. When the giraffe mutation was inserted into the FGFRL1 gene in mice, significantly less renal and heart fibrosis was observed during hypertension [72]. Thus, as the giraffe FGFRL1 gene counteracts the detrimental effects of hypertension, it may hold a clue for treatments to protect humans from the adverse effects of hypertension.…”
Section: Cancer Protective Solutions In Naturementioning
confidence: 99%